1963
DOI: 10.1099/00221287-31-3-495
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscopic Observation of the Sporangial Structure of an Actinomycete, Microellobosporia flavea

Abstract: SUMMARYUltrathin sections of sporangia of the actinomycete Microellobosporiu JEavea were examined with an electron microscope. The sporangial wall is a thin, wrinkled membrane which seems to be an extension of the outer layer of the cell wall of the sporangiophore. A substance, probably a liquid, is located between the sporangial wall and the sporangiospores. The spores are ovoid and consist of a laminated wall in which two layers can be differentiated. The wall is 30-40 mp thick but thickens to 90-120 mp a t … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

1965
1965
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…A comparison of our sections of this strain of Actinoplanes with those lpublished for Alicroellobosporia favea (Rancourt and Lechevalier, 1963) and for a Streptosporangium strain (Rancourt, 1963) revealed that, whereas the strains of Actinoplanes and M1Iicroellobosporia had an intersporal substance, the strain of Streptosporangium did not. On the basis of the published information and some unpublished data on a strain of Streptosporangium, we believe, at the moment, that these three types of sporangia-bearing actinomycetes form their spores in about the same manner.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…A comparison of our sections of this strain of Actinoplanes with those lpublished for Alicroellobosporia favea (Rancourt and Lechevalier, 1963) and for a Streptosporangium strain (Rancourt, 1963) revealed that, whereas the strains of Actinoplanes and M1Iicroellobosporia had an intersporal substance, the strain of Streptosporangium did not. On the basis of the published information and some unpublished data on a strain of Streptosporangium, we believe, at the moment, that these three types of sporangia-bearing actinomycetes form their spores in about the same manner.…”
mentioning
confidence: 70%
“…He named these organisms Actinoplanes and added the family Actinoplanaceae to the Actinomycetales (Couch, 1955a, b). Other sporangia-bearing actinomycetes came to be recognized, and so far a total of five genera have been proposed by Couch (1963Couch ( , 1964 and one by Cross, Lechevalier, and Lechevalier (1963). The morphological differences between these various organisms can be summarized in the following key to the genera of the family Actinoplanaceae.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Coincidentally, the sheath with a crevice was gone from those flagellated spores. There have been no reports on whether spores in sporangia have an extra sheath over the cell wall (3,11,12,18,19). We suspect that spores right after release from sporangia might still be wrapped with that newly found membranous sheath, and by unwrapping the sheath from the spore in a similar manner as ecdysis, flagella would be exposed and become free to move.…”
mentioning
confidence: 99%
“…In previous publications, we reported on the ultramicroscopic structure of strains of Microellobosporia (17) and Actinoplanes (13). In the case of the Actinoplanes sp., observation of ultrathin sections showed that a branched and coiled hypha grew inside a sporangial envelope and that its almost simultaneous division, perpendicular to its long axis, resulted in the formation of sporangiospores.…”
mentioning
confidence: 99%